Disputa pela terra em Moçambique - caso do distrito de Marracuene - Yung, Telma Leo (2024)
The research was carried out within the scope of the Graduate Program in Environmental Sciences, with the aim of investigating land access and tenure in the Marracuene District, Mozambique. The main focus is to identify the main factors that cause land disputes in the study area, with an emphasis on the point of view of traditional producers. The increase in the demand for land in the district is driven by several factors, such as the geographical proximity to Maputo city, the "Maputo Ring Road", the Bridge over the Incomati River that connects Macaneta and the holding of the "Maputo International Fair - FACIM". In addition, the purpose of housing and investments in sectors such as trade, agriculture and tourism also contribute to the pressure on land. The combination of these factors contributes to an increase in demand for land in the district, generating pressure on land, boosting the economic, social and environmental development of the region. To investigate this, the study adopted mixed research procedure techniques, relying on field observations, questionnaires and interviews. Based on data collected in the field and information provided by the Serviço Distrital de Planeamento e Infra - Estruturas (SDPI), we identified four communities facing disputes over land, involving different actors, being: (1) Marracuene Vista Company, Traditional Leaders and the neighborhood Mapulango; (2) Community of Eduardo Mondlane I and Regulus Magaia; (3) Guava Peasant Association and the Korean Mission; (4) Community of the neighborhood of Zintava and Sr. Milton Torre de Vale and Fundo para o Fomento e Habitação (F.F.H). To resolve these disputes, the parties involved are invited to participate in conciliation processes, mediated by the Land Chiefs, with the assistance of the Regulus. In some cases, the block chief and Neighborhood Secretary may also be involved, depending on the nature of the conflict or dispute. In situations considered difficult to resolve, cases related to land disputes in Marracuene can be referred to higher instances, such as the 2nd and 1st levels, including at the locality level, the Administrative Post and, finally, the District Administration. The Dispute Resolution Committee, present at the SDPI (Serviço Distrital de Planeamento e Infra- Estruturas), also plays an important role in the mediation and arbitration process. These higher authorities are called upon to seek more comprehensive and complex solutions, in order to achieve a fair and adequate resolution to land disputes or conflicts. The district of Marracuene is going through a period of expansion marked by the transition from an agrarian base to latent urban growth, dissociated from the industrialization process. This transition highlights urbanization associated with commercialization, reflected in the increase in land prices and the boost in the tourism sector. However, this process has been accompanied by the destruction of agrarian and peasant life, resulting in a totalizing social dynamic of urban society and the perception among interviewees reveals concerns about the loss of agricultural land, resettlement without adequate compensation and corruption in the bodies of dispute resolution. With all this, these interests often trigger territorial disputes and environmental degradation. The necessary approach must reconcile socioeconomic development with environmental preservation and social justice, requiring the effective implementation of public policies and the protection of the rights of local communities to ensure fair and sustainable land management.